2017
DOI: 10.1167/iovs.17-22159
|View full text |Cite
|
Sign up to set email alerts
|

Colony Stimulating Factor-1 Receptor Expressing Cells Infiltrating the Cornea Control Corneal Nerve Degeneration in Response to HSV-1 Infection

Abstract: PurposeHerpes simplex virus type-1 (HSV-1) is a leading cause of neurotrophic keratitis, characterized by decreased or absent corneal sensation due to damage to the sensory corneal innervation. We previously reported the elicited immune response to infection contributes to the mechanism of corneal nerve regression/damage during acute HSV-1 infection. Our aim is to further establish the involvement of infiltrated macrophages in the mechanism of nerve loss upon infection.MethodsMacrophage Fas-Induced Apoptosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…Flow cytometric characterization of the cellular component that infiltrates the corneas of mice following reactivation revealed that the total number of inflammatory cells in wild-type mice significantly eclipsed that seen in their CD28KO counterparts. This observation was exactly as we predicted from the clinical scores and consistent with previous literature on this aspect of disease (3,(33)(34)(35). While B6-CD28KO mice did develop an inflammatory infiltrate consisting of CD4 ϩ T cells, CD8 ϩ T cells, neutrophils, and macrophages, their numbers were significantly less that that observed for wildtype B6 mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Flow cytometric characterization of the cellular component that infiltrates the corneas of mice following reactivation revealed that the total number of inflammatory cells in wild-type mice significantly eclipsed that seen in their CD28KO counterparts. This observation was exactly as we predicted from the clinical scores and consistent with previous literature on this aspect of disease (3,(33)(34)(35). While B6-CD28KO mice did develop an inflammatory infiltrate consisting of CD4 ϩ T cells, CD8 ϩ T cells, neutrophils, and macrophages, their numbers were significantly less that that observed for wildtype B6 mice.…”
Section: Discussionsupporting
confidence: 92%
“…Recurrent infection causes an immunopathologic condition that leads to corneal inflammation and chronic damage. Previous studies have demonstrated that HSK requires intact T cells (17)(18)(19)(20) and an inflammatory infiltrate that consists of both neutrophils (15,33) and macrophages (34,35). Our present study extends those studies by indicating that CD28 costimulation of T cells is necessary for both primary and recurrent disease.…”
Section: Discussionsupporting
confidence: 83%
“…The supernatants from tissue homogenates were assayed for protein content using a BCA protein method (#23225; ThermoFisher Scientific) and along with diluted plasma samples, used for protein analyses. Suspension array analyte concentrations were determined using a Bio-Rad Bio-Plex System Luminex 100 and Bio-Plex manager 5.0 (Bio-Rad Laboratories, Hercules, CA) 40 . Milliplex Map luminex-based assays were used to quantify the mouse inflammatory cytokines IL-6, TNFα, and INFɣ (#MCYTOMAG-70K; EMD Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
“…For secondary chemiluminiscent detection, blots were incubated with corresponding HRP-conjugated secondary antibodies (GE Healthcare Bio-Sciences, Pittsburgh, PA). Imaging of the blots and analysis of band intensities were performed by conventional image analysis using a Kodak in vivo imaging system F Pro and Carestream MI SE 4.4 SE version software (Carestream Health, Inc., Rochester, NY) [(Chucair-Elliott et al 2017)]. Two-way ANOVA analyses were performed with the factors of sex and treatment.…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%